2020
DOI: 10.3390/ijerph17124244
|View full text |Cite
|
Sign up to set email alerts
|

When Is the Negative Effect of Abusive Supervision on Task Performance Mitigated? An Empirical Study of Public Service Officers in Korea

Abstract: Supervisory leadership has occupied an important place in management literature in identifying the supervisory behaviors that are associated with positive outcomes. However, researchers also have turned their attention to the dark side of supervisory behavior, such as abusive supervision. This study investigates the role of coworker support and self-efficacy in the relationship between abusive supervision and the subordinate’s task performance. Data are collected from 192 supervisor–subordinate pairs in the So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Self-efficacy, which is defined as an individual's belief in his or her own ability to carry out certain tasks, plays an important role in shaping a person's response to abusive supervision. When individuals have confidence in their abilities, they may resist negative treatment from supervisors (Park et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy, which is defined as an individual's belief in his or her own ability to carry out certain tasks, plays an important role in shaping a person's response to abusive supervision. When individuals have confidence in their abilities, they may resist negative treatment from supervisors (Park et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars had indicated the positive impact of leadership in public sectors (Alimo-Metcalfe and Alban-Metcalfe, 2006;Anne Loewenberger et al, 2014;Tuan, 2016;Ugaddan and Park, 2017). In the last five years, more studies found the negative effect of destructive leader behaviours in public organisations (Gabriel, 2016;Khan et al, 2020;Park et al, 2020;Vogel et al, 2016).…”
Section: Effect Of Toxic Leadership 317mentioning
confidence: 99%
“…In the last five years, more studies found the negative effect of destructive leader behaviours in public organisations (Gabriel, 2016; Khan et al. , 2020; Park et al. , 2020; Vogel et al.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have discussed how discriminatory culture against women can promote gender inequality at work, women's career under-achievement, discriminatory behavior against women and work-family conflict (Trzebiatowski and Triana, 2020). Under the pressure of a discriminatory culture, female workers have suffered from sexual harassment, the main form of workplace discrimination (Park et al, 2020). When employees experience discrimination in their organization, it can lead to emotional exhaustion and role stress, resulting in heavier work-family conflict (Trzebiatowski and Triana, 2020).…”
Section: Key Constructs and Theoretical Backgroundmentioning
confidence: 99%
“…As a form of gender discrimination in the workplace, sexual harassment puts women at risk of stress and mental instability at work, which can harm their mental health (Kim et al, 2022). Sexual harassment or bullying in the workplaces victimizes female workers and destabilizes their work and family lives (Park et al, 2020).…”
Section: Introductionmentioning
confidence: 99%